Wheat bran with enriched gamma-aminobutyric acid attenuates glucose intolerance and hyperinsulinemia induced by a high-fat diet. Issue 5 (25th April 2018) - Shang, Wenting; Si, Xu; Zhou, Zhongkai; Strappe, Padraig; Blanchard, Chris
Abstract : In this study, the level of gamma-aminobutyric acid in wheat bran was increased to be six times higher and the new bran had a greater capacity for weight control in high-fat diet than untreated bran. Abstract : In this study, the level of gamma-aminobutyric acid (GABA) in wheat bran was increased to be six times higher through the action of endogenous glutamate decarboxylase compared with untreated bran. The process of GABA formation in wheat bran also led to an increased level of phenolic compounds with enhanced antioxidant capacity 2 times higher than the untreated status. The interventional effect of a diet containing GABA-enriched bran on hyperinsulinemia induced by a high-fat diet (HFD) was investigated in a rat model. The results showed that, when compared with animals fed with HFD-containing untreated bran (NB group), the consumption of HFD-containing GABA-enriched bran (GB group) demonstrated a greater improvement of insulin resistance/sensitivity as revealed by the changes in the homeostatic model assessment for insulin resistance index (HOMA-IR) and the quantitative insulin sensitivity check index (QUICKI). The expression of hepatic genes, cytochrome P450 family 7 subfamily A member 1 ( Cyp7a1 ) and ubiquitin C ( Ubc ), which are involved in the adipogenesis-associated PPAR signalling pathway, was found to be significantly down-regulated in the GB group compared with the HFD group ( P = 0.0055). Meanwhile, changes in the expression of a number of genes associated with lipid metabolism and gluconeogenesis were also noted in the GB group versus the HFD group, but not in the NB group, indicating different regulatory patterns between the two brans in a high-fat diet. More importantly, the analysis of key genes related to glucose metabolism further revealed that the expression of insulin-induced gene 1 / 2 ( Insig-1 / 2 ) was increased following GB intervention with a corresponding reduction in phosphoenolpyruvate carboxykinase 1 ( Pepck ) and glucose-6-phosphatase, catalytic subunit ( G6pc ) expression, suggesting that glucose homeostasis is greatly improved through the intervention of GABA-enriched bran in the context of a high-fat diet.